Work-Family Conflict on Turnover Intentions Mediating Role of Psychological Well-Being - Tiara Arieza Fitrizqa; Adiatma Yudistira Manogar Siregar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
High turnover intention among married female nurses at Fatmawati Hospital increases operational costs and risks compromising the quality of healthcare services. This study investigated the impact of work-family conflict (WFC) on turnover intention (TI), emphasizing the mediating role of psychological well-being (PWB). Using a mixed-methods approach, primary data were collected through structured questionnaires from married female nurses, while secondary data supported the theoretical framework. WFC was measured through two dimensions: work interference with family and family interference with work. PWB encompasses six dimensions, and TI was assessed based on six indicators related to job satisfaction and turnover intention. Data analysis using SPSS revealed that WFC negatively impacted PWB and positively impacted TI. In addition, higher psychological well-being reduced turnover intention and partially mediated the WFC–TI relationship. These findings highlight the importance of managing work-family conflict and improving nurses’ psychological well-being to reduce turnover risk. Limitations include a single hospital sample and cross-sectional design, and the need for larger longitudinal studies that can incorporate qualitative insights.